Development of Integrated Thematic Teaching Materials With Project Based Learning Models in Class IV of Primary Schools - Ijal, Syafrijal; Desyandri, Desyandri (International Journal of Educational Dynamics, 2019)
This research is a development research on teaching materials in the fourth grade of elementary school. This research uses Research and Development (R & D) research with the 4D Model. This teaching material was developed using the four D model (4-D), namely define, design, develop and disseminate. The stage of dissemination (disseminate) is only done on a limited scale, namely at SDN 14 Gunung Sarik, Kota Padang. The results of the RPP validity were declared valid with an average of 89.66%. The results of the average teaching material obtained 93.39% from expert validators and 92.8% from practical validators with very valid categories. The practical test results from the implementation of the lesson plan with a percentage of 87.92% with a very practical category. Assessment of teacher responses obtained 91.22% and assessment of student responses 92.08% with a very practical category. Assessment of student activities obtained 77.28 active categories. Learning outcomes assessment shows that the percentage of completeness results above the KKM. Based on these results, it can be concluded that thematic teaching materials with the Project Based Lerning (PjBL) model for elementary school fourth grade students are valid, practical, and effective